2018
DOI: 10.1536/ihj.17-290
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA DIGIT Accelerates Tube Formation of Vascular Endothelial Cells by Sponging miR-134

Abstract: Atherosclerosis is one of the most prevalent and important cardiac diseases, involving the heart and brain. This study aimed to explore the impacts of lncRNA Divergent to GSC induced by TGF-b family signaling (DIGIT) on vascular endothelial cells tube-formation capacity so as to reveal the potentials of DIGIT in atherosclerosis therapy. DIGIT expression in human microvascular endothelial HMEC-1 cells was silenced by transfection with shRNAs-targeted DIGIT. The effects of DIGIT silence on cell viability, migrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 33 publications
(43 reference statements)
0
10
0
Order By: Relevance
“…Atherosclerosis is one of the leading causes of myocardial infarction in the world. 1 In fact, atherosclerosis is a multistep disease, which results from multiple risk factors, 2 , 3 including dysfunction of HUVECs. 4 Various dysfunctions of HUVECs including inappropriate proliferation, migration and apoptosis are critical cellular events resulting in the occurrence and development of atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…Atherosclerosis is one of the leading causes of myocardial infarction in the world. 1 In fact, atherosclerosis is a multistep disease, which results from multiple risk factors, 2 , 3 including dysfunction of HUVECs. 4 Various dysfunctions of HUVECs including inappropriate proliferation, migration and apoptosis are critical cellular events resulting in the occurrence and development of atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…We were interested in miR‐134‐5p because it has been reported that it is one of the miRNAs up‐regulated in the serum of patients with coronary artery calcification 26 . Also, in endothelial cells, miR‐134‐5p is related to tumour angiogenesis 27 and endothelium‐associated cardiac tube formation during development 28 . More recently, miR‐134‐5 p was shown to be involved in VSMC phenotypic switching and migration and in the progression of thoracic aortic dissection 29 .…”
Section: Resultsmentioning
confidence: 99%
“…The function of miR‐134 has also been investigated in cardiovascular diseases, although fewer studies have been reported than for the nervous system or cancer. In the embryo, miR‐134 regulates endothelium‐linked cardiac tube formation through down‐regulation of polycomb complex protein BMI‐1 28 . Wu et al reported that miR‐134 directly targets myeloid ecotropic insertion site 2 and promotes human cardiomyocyte precursor cell proliferation 55 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations